'Land-use mixité': Evaluating urban hierarchy and the urban-to-rural gradient with an evenness-based approach. (November 2016) - Salvati, Luca; Sateriano, Adele; Saradakou, Efthimia; Grigoriadis, Efstathios
Abstract: This study illustrates an original approach to assess city hierarchy in metropolitan regions and to investigate urban gradients using local-scale socioeconomic data. By linking land-use to the diversification in the level of land imperviousness, we consider fragmentation and diversity in the use of land to distinguish urban from rural areas. We applied an entropy function to a map of land imperviousness in Athens' metropolitan region, Greece, with the aim to classify municipalities into urban and rural types based on Shannon diversity and Pielou evenness indexes. Urban areas are hypothesized to have higher diversification in the degree of imperviousness than rural areas. Principal Component Analysis and Canonical Correlation Analysis were used to verify the spatial coherency between land imperviousness and the distribution of urban land-use. Land imperviousness Pielou index increased linearly with both diversity in the use of land and ancillary variables assessing the urban gradient (population density and distance from the inner city). Our study identifies urban and rural municipalities respectively as the most and the less diversified in terms of land-use and imperviousness intensity, with suburban areas ranking in-between. Pielou evenness index applied to land imperviousness maps and the notion of land-use diversification are promising tools to monitoring city hierarchy along urban gradients.